Incidence and Characterization of Salmonella Isolates From Raw Meat Products Sold at Small Markets in Hubei Province, China - Zhou, Min; Li, Xiaofang; Hou, Wenfu; Wang, Hongxun; Paoli, George C.; Shi, Xianming (Frontiers in Microbiology, 2019)
Salmonella is a leading cause of foodborne disease especially through contaminating animal products. In this study, 66 Salmonella isolates were obtained from 631 retail raw meat samples in Hubei Province, China. The most prevalent serotypes were Salmonella Thompson (18.2%) and Salmonella Agona (13.6%). Multilocus sequence typing analysis revealed 32 sequence types, ST26 (18.2%) and ST541 (12.1%) predominated. Our results indicated that these isolates were phenotypically and genetically diverse. High antimicrobial resistance was observed for the sulphonamides (43.9%), tetracycline (43.9%), amoxicillin (36.4%) and ampicillin (36.4%). Interestingly, high-level resistance to cephazolin was observed in dominant S. Thompson isolates. Class I integrons were found in 27.3% (18/66) of the isolates and these contained 5 gene cassettes (aacA4C-arr-3-dfr2, dfrA12-aadA21, aadA2, dfrA12-aadA2, dfr17-aadA5). Class I integron positive isolates were significantly more resistant to multiple antimicrobials. The antimicrobial phenotypes were positively correlated with possession of corresponding resistant genes and the sul1, tetA, floR, blaTEM and qnrB genes were the most prevalent. The decreased susceptibility to cephalosporins and fluoroquinolones in some of these isolates are an important public health concern.